The extent to which the Social Security Institution in Jordan adheres to the requirements of International Accounting Standard No (19) for employee benefits - SAYYED, SALEH MOHAMMAD MAHMOUD AL; OTHMAN, DR.OTHMAN HUSSEIN OTHMAN; HUSSEIN, HUSSEIN OTHMAN; ALHARASEES, ABDALLAH SULEIMAN MAHMOUD (The journal of contemporary issues in business and government, 2021)
This study aimed to identify the extent to which the Social Security Institution in Jordan adheres to the requirements of International Accounting Standard No (19) related to employee benefits. The study population included the Social Security Institution in Jordan. As for the sample, it consisted of (78) respondents from financial managers, department heads and their deputies, and accountants working in the financial and accounting departments in the institution. The study found that the institution adheres to the requirements of International Accounting Standard No (19) for short-term and long- term employee benefits, and is also committed to post-service employee benefits and end- of-service benefits. It turned out that the level of this commitment was at a high level. The study recommended the provision of optional and mandatory burdens to the beneficiary within the framework of individual institutions, and the provision of salaries and wages in exchange for performing the service with the associated social and tax burdens.